Mycotoxin Identification and In Silico Toxicity Assessment Prediction in Atlantic Salmon - Josefa Tolosa; Francisco J. Barba; Noelia Pallarés; Emilia Ferrer (Marine Drugs, 2020)
The present study aimed to identify mycotoxins in edible tissues of Atlantic salmon (Salmo salar) using liquid chromatography coupled to hybrid quadrupole time-of-flight mass spectrometry (LC-Q-TOF-MS). After using a non-targeted screening approach and a home-made spectral library, 233 mycotoxins were analyzed. Moreover, the occurrence of mycotoxins in fish filets was evaluated, and their potential toxicity was predicted by in silico methods. According to the obtained results, forty mycotoxins were identified in analyzed salmon samples, the predominant mycotoxins being enniatins (also rugulosin and 17 ophiobolins), commonly found in cereals and their by-products. Thus, mycotoxin carry-over can occur from feed to organs and edible tissues of cultivated fish. Moreover, the toxicity of detected mycotoxins was predicted by the in silico webserver ProTox-II, highlighting that special attention must be paid to some less reported mycotoxins due to their toxic predicted properties.